Heterogeneity and high prevalence of bone manifestations, and bone mineral density in congenital generalized lipodystrophy subtypes 1 and 2 - Freire, Erika Bastos Lima; Brasil d’Alva, Catarina; Madeira, Mayara Ponte; Lima, Grayce Ellen da Cruz Paiva; Fernandes, Virginia Oliveira; Aguiar, Lindenberg Barbosa; Portella, Leonardo Barreira; Galvão Ozório, Renan; Ponte, Clarisse Mourão Melo; Montenegro, Ana Paula Dias Rangel; Montenegro Junior, Renan Magalhães (Frontiers in Endocrinology, 2024)
Introduction: Congenital Generalized Lipodystrophy (CGL) is a rare autosomal recessive disease caused by mutations in genes responsible for the formation and development of adipocytes. Bone abnormalities are described. However, there is a scarcity of data. Objective: To describe bone characteristics in a large CGL1 and 2 case series. Methods: Cross-sectional study that assessed bone radiological features of CGL patients of a reference hospital in Fortaleza (CE), Brazil. Patients underwent clinical and bone mineral metabolism evaluation, radiographs of the axial and appendicular skeleton and bone mineral density (BMD) assessment by DEXA (dual energy X-ray absorptiometry). Results: Nineteen patients were included, fourteen were CGL1 and 5, CGL2. Median age was 20 years (8-42) and 58% were women. Median BMI and percentage of body fat were, respectively, 21 Kg/m² (16-24), and 10.5 % (7.6-15.) The median leptin concentration was 1 ng/mL (0.1-3.3). Diabetes mellitus and dyslipidemia were present in 79% and 63% of patients, respectively. Median calcium and phosphate were normal in almost all patients (95 %). Median parathyroid hormone and 25-OH-vitamin D were 23 pg/mL (7-75) and 28 ng/mL (18-43). Osteolytic lesions, osteosclerosis and pseudo-osteopoikylosis, were present in 74%, 42% and 32% of patients, respectively. Lytic lesions were found predominantly in the extremities of long bones, bilaterally and symmetrically, spine was spared. Osteosclerosis was present in axial and appendicular skeleton. Pseudo-osteopoikilosis was found symmetrically in epiphyses of femur and humerus, in addition to the pelvis. BMD Z-score greater than +2.5 SD was observed in 13 patients (68.4%). BMD was higher in CGL1 compared to CGL2 in lumbar spine and total body in adults. No associations were found between high BMD and HOMA-IR (p=0.686), DM (p=0.750), osteosclerosis (p=0.127) or pseudoosteopoikilosis (p=0.342), and, between pain and bone lesions. Fractures were found in 3 patients. Conclusion: Bone manifestations are prevalent, heterogeneous, and silent in CGL1 and CGL2. Osteolytic lesions are the most common, followed by osteosclerosis and pseudo-osteopoikilosis. Bone mass is high in most cases. There was no pain complaint related to bone lesions. Thus, systematic assessment of bone manifestations in CGL is essential. Studies are needed to better understand its pathogenesis and clinical consequences.